Cultural variations and business performance : contemporary globalism - Christiansen, Bryan, 1960- (Business Science Reference, 2012)
"This book offers the latest research in the field of Business Performance Management in the global economic environment of present conditions while looking at business as a whole entity instead of only at the divisional level"--Vydavatelská anotace
"Premier reference source"--Z obálky
Keywords: interkulturní management; mezinárodní podnikání; organizační chování; globalizace; intercultural management; international business; organizational behavior; globalization; sborníky; papers of several authors